LEGAL REVIEW OF THE PROTECTION OF CHILDREN'S RIGHTS IN TERMS OF MAINTENANCE RIGHTS AS A RESULT OF DIVORCE BASED ON THE VALUES OF JUSTICE A STUDY OF DECISIONS IN THE TANJUNG BALAI RELIGIOUS COURT - Eddy Sumardi; Henry Aspan; Andoko , Andoko (International Journal of Synergy in Law, Criminal, and Justice, 2025)
Divorce not only affects the relationship between husband and wife, but also has serious consequences for children, especially in terms of custody and support. In the Indonesian legal system, child maintenance rights after divorce are regulated in Law Number 1 of 1974 concerning Marriage which has been amended by Law Number 16 of 2019 and Law Number 35 of 2014 concerning Child Protection. The main principle in determining custody rights is the best interest of the child, as stated in national and international law. In Islamic law, hadhanah is generally given to the mother, especially for children who are not yet mumayyiz. This study aims to analyze legal protection of children's rights in post-divorce maintenance through a case study of the Tanjung Balai Religious Court's decision. The results of the study indicate that there are challenges in the implementation of court decisions, especially in the execution of custody rights and the fulfillment of child support. In some cases, court decisions are not followed by an effective execution mechanism, causing children's rights not to be fully fulfilled. Therefore, a clearer legal reconstruction is needed regarding post-divorce child care, including strengthening regulations regarding child support and the execution of court decisions. In addition, the shared parenting approach can be an alternative in maintaining children's welfare while still involving both parents in their care.